Penerapan Konsep Manajemen Rantai Pasok Pada Produk Unggas - nFN Saptana; Rangga Ditya Yofa (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 2016)
EnglishMarketing and logistics experts pay great attention to the concept of supply chain management and try to operationalize in agricultural development especially for high-value products, such as poultry products. The supply chain management concept is interpreted from various perspectives including marketing and logistics perspectives. This paper aims to analyze (1) a conceptual review of supply chain management; (2) the dynamics of production and consumption of poultry products; (3) performance of supply chain management on poultry products; and (4) integrated supply chain management strategy formulation for poultry products. This study applies analysis of review from various sources of literature, primary journals, research results, and text books. A review of the conceptual aspects of supply chain management has identified the different concepts of marketing with supply chain management. Supply chain management analysis on poultry products can improve poultry product distribution efficiency through product process integration among the actors. Production and consumption performance of poultry products showed a high increase, but its trade position is still deficit. In order to realize an efficient distribution system of poultry products, it is necessary to implement integrated supply chain management. In this context, the government needs to facilitate growth and development of poultry agribusiness partnership through integrated supply chain management approach.IndonesianPakar pemasaran dan logistik memberikan perhatian besar terhadap konsep manajemen rantai pasok dan mencoba mengoperasionalkan dalam pembangunan pertanian, terutama pada produk bernilai ekonomi tinggi, seperti produk-produk perunggasan. Konsep manajemen rantai pasok dimaknai dari berbagai perspektif, antara lain perspektif pemasaran dan logistik. Tulisan ini bertujuan untuk (a) meng-analisis konsep manajemen rantai pasok; (b) mengkaji dinamika perkembangan produksi dan konsumsi produk unggas; (c) mengkaji kinerja manajemen rantai pasok produk unggas; dan (d) merumuskan strategi manajemen rantai pasok produk unggas secara terpadu. Metode yang digunakan adalah analisis review dari berbagai sumber pustaka, baik jurnal primer, hasil penelitian, dan buku-buku terkait topik tulisan. Tinjauan dari aspek konseptual manajemen rantai pasok telah berhasil mengidentifikasi perbedaan konsep pemasaran dengan manajemen rantai pasok. Penggunaan analisis manajemen rantai pasok pada produk perunggasan dapat meningkatkan efisiensi distribusi produk perunggasan melalui keterpaduan proses produk dan antarpelaku dalam rantai pasok. Kinerja produksi dan konsumsi produk perunggasan menunjukkan peningkatan yang tinggi, namun posisi perdagangannya hingga kini masih defisit. Dalam rangka mewujudkan sistem distribusi produk perunggasan yang efisien diperlukan penerapan manajemen rantai pasok secara terpadu. Dalam hal ini, pemerintah perlu memfasilitasi bagi tumbuh dan berkembangnya kemitraan usaha agribinis perunggasan melalui pendekatan manajemen rantai pasok secara terpadu.